Seasonal variation in agar composition and properties from Gracilaria gracilis (Gracilariales, Rhodophyta) of the Patagonian coast of Argentina - Martin, Lucas Ariel (2013)
Seasonal variation of agar from specimens of a commercially exploited population of Gracilaria gracilis (Stackhouse) Steentoft, Irvine & Farnham in the Patagonian coast of Argentina was studied. For each seasonal harvest, random samples of plants were pooled for subsequent polysaccharide extraction at different water temperatures and agar physico-chemical properties and composition were determined. Both spring and summer plants yielded 30% and 41% of agar, respectively, which differed slightly in their at rest rheological behavior. Spring and summer plants produced strong gels (238 and 218 g cm-2 , respectively), but the latter gels had nil adhesiveness. In autumn plants, agar yield decayed to 19%, though the product still maintained similar gel strength (210 g cm-2 ). Adhesiveness in this product was at least an order of magnitude higher than in the others, concomitant with a peak in the formation of tetraspores and carpospores. This suggests a biological role for the galactan in the initial attachment of spores to the substrate. But since fall corresponds to the settling of reproductive structures, caution should be taken to harvest the algae once spores have been shed from mother plants.